Ultrasonic-Assisted Dual-Alkali Pretreatment and Enzymatic Hydrolysis of Sugarcane Bagasse Followed by Candida tropicalis Fermentation to Produce Xylitol - Gai, Lili; Ren, Er-Fang; Tian, Wen; Niu, Debao; Sun, Weidong; Hang, Fangxue; Li, Kai (Frontiers in Nutrition, 2022)
In this work, the investigation mainly focused on ultrasonic-assisted dual-alkali pretreatment and enzymatic hydrolysis of sugarcane bagasse followed by Candida tropicalis fermentation to produce xylitol. The results showed that the combination of NaOH and ammonia water had the best effect by comparing the effects of the four single-alkali (NaOH, KOH, ammonia water, Ca(OH)2) and their mixed double-alkali pretreatments on xylose content. Then, the optimal conditions for ultrasonic-assisted pretreatment and enzymatic hydrolysis of sugarcane bagasse were obtained by response surface methodology. When the ratio of NaOH and ammonia water was 2:1, the mixed alkali concentration (v/v) was 17%, the ultrasonic temperature was 45 ℃, the ultrasonic power was 300 W, and the ultrasonic time was 40 min, the content of xylose reached a maximum of 2.431 g/L. Scanning electron microscopy showed that sugarcane bagasse by ultrasonic-assisted alkali pretreatment aggravated with more folds and furrows. Moreover, the fermentation results showed that the concentration ratio of enzymatic hydrolysate of sugarcane bagasse affected the xylitol yield, and when concentrated three times, the highest yield of xylitol (54.42%) was obtained.